Personality Moderation in the Perspective of Islamic Psychology: A Study of the Works and Teachings of Ibn Miskawaih - Novalia, Rifyal; Kusayang, Titin; Vitaloka, Wulansari (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2023)
This study aims to look at the various virtues of the soul that become the midpoint in behavior, these virtues are the virtues between the two vices of extreme excess and neglect. Because moderation is the midpoint between these two attitudes. Departing from the above statement, the attitude that contradicts the moderate attitude certainly cannot be used as a reference to create a conducive atmosphere, both in terms ofsociety and individual life. Moreover, doctrines that suggest a liberal way of thinking and individualism cannot be used as a reference and view to create harmony and balance in life. Ibn Miskawaih in the book Tahdhib Alakhlaq wa Tathir al-A'raq excessive and defi ciency is a bad thing while moderation is a virtue and even a virtue in the psychological system. Excessive extremes are characterized by behavioral recklessness, arbitrary and free to do according to their own wishes regardless of the prevailing norms. This is not a gentle attitude from religious teachings that always echo the values of al-rahmat al-alamin which should be the attitude of a Muslim. This research is a literature review, exploring relevant sources such as articles, journals, books, and other documents that describe theories and information both past and present organizing the literature into the topics and documents needed. By sourcing the works and teachings of Ibn Miskawaih, namely Tahdib al-Akhlaq wa Tathir al-A'raq The approach used in this research is a psychological approach. The findings of this study produce a statement that the attitude of moderation when implemented specifically for individuals will make a moderate person towardssociety, mental and spiritual values. Penelitian ini bertujuan untuk melihat berbagai macam kebajikan jiwa yang menjadi titik tengah dalam bersikap, kebajikan tersebut merupakan keutamaan antara dua keburukan yakni ekstrem berlebihan dan terlalu mengabaikan. Oleh sebab moderasi merupakan titik tengah diantara dua sikap tersebut. Berangkat dari pernyataan diatas, maka sikap yang bertolak belakang dengan sikap moderat tentunya tidak dapat dijadikan sebuah acuan untuk menciptakan suasana kondusif, baik ditilik dari segi kehidupan sosial maupun individual. Terlebih lagi doktrin yang mengemukakan cara berfikir yang liberal dan individualisme tidak dapat dijadikan sebuah acuan dan pandangan untuk menciptakan keselarasan dan keseimbangan dalam kehidupan. Ibn Miskawaih dalam kitab Tahdhib Alakhlaq wa Tathir al-A’raq berlebihan dan kekurangan merupakan suatu keburukan sedangkan sifat moderat (moderasi) adalah suatu kebajikan bahkan merupakan suatu keutamaan dalam sistem kejiwaan. Sikap ekstrem berlebihan ditandai dengan kegarangan perilaku, semena-mena, dan bebas berbuat sesuai dengan keinginan sendiri tanpa memandang norma yang berlaku. Hal tersebut bukanlah sikap lembut dari ajaran agama yang selalu menggabungkan nilai-nilai ke al-rahmat al-alamin yang seharusnya menjadi sikap sebagai seorang muslim. Penelitian ini bersifat kajian literatur, menggali sumber yang relevan seperti artikel, jurnal, buku, dan dokumen lain yang mendeskripsikan teori serta informasi baik masa lalu maupun saat ini mengorganisasikan pustaka ke dalam topik dan dokumen yang dibutuhkan. Dengan bersumber pada karya dan ajaran Ibnu Miskawaih yakni Tahdib al-Akhlaq wa Tathir al-A’raq Adapun pendekatan yang digunakan dalam penelitian ini adalah pendekatan psikologis. Adapun temuan dari penelitian ini menghasilkan pernyataan, bahwa sikap moderasi apabila diimplementasikan secara khusus bagi individu akan menjadikan pribadi yang moderat terhadap nilai-nilai sosial, mental dan spiritual.